Trust Building and Fake News on Social Media from the Perspective of University Students from Four Visegrad Countries - Eger, Ludvík; Egerová, Dana; Mičík, Michal (Communication Today, 2020)
There is an important need in the literature to explore the effects of social media use on young people’s behaviour. The main purpose of this research is to explore which factors of users’ gratiﬁcations are associated with using social media by university students from four Visegrad countries in Central Europe. Online communication on social media may be affected by a variety of factors that affect the development of mutual relationships. Thus, research is also focused on trust building on social media. The research team conducted qualitative research aimed at the deeper understanding of students’ opinions on trust and social media and their view on the phenomenon of “fake news”. Conducted focus groups in four countries showed that university students, who are frequent users of social media, are inclined to trust certain pages they like but generally, they do not trust social media. They use social media primarily for maintaining relationships and they believe people who are connected to their network. It is obvious that students use social media to satisfy their needs, especially in the ﬁeld of entertainment, partly also for obtaining information. The ﬁndings show that expected gratiﬁcations of students are built on their practical experience with media.